Core Problem Solving (CPS) – Kepner Treg Approach to strengthen quality performance at PT. UTC Aerospace System Bandung (UTAS Bandung) - Erwan Nofrianto; Mursyid Hasan Basri (Review of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This research aims to determine the effectiveness of Core Problem Solving (CPS) with the Kepner Tregoe approach, which is able to improve %SRR performance from 0.73% in 2022 to 0.5% in the next five years and take the right solutions to be planned in 2023. Methods: A study on this case at UTAS Bandung with a focus on the %SRR performance that is driven by the amount of scrap, rework, and repair parts, called the cost of poor quality (CoPQ) divided by the total amount of parts sold to the customer. Core Problem Solving (CPS) combined with the Kepner Treg method can strengthen the quality performance. Starting with problem identification, followed by problem analysis using a Pareto diagram, an ishikawa diagram (fishbone diagram), and five why analysis to obtain the correct root cause and come out with alternative solutions to prevent future faults. Results/findings: Based on problem analysis, it was found that the highest CoPQ contributor comes from prismatic cells, around 61% or $154,000 of total CoPQ $254,300 in 2022. To reach a 0.5% target in 2027 need to improve around $81,115 within 5 years or similar with $16,223 per year. Core problem solving (CPS) combined with the Kepner Treg method will be applied to achieve quality performance as planned. Limitations: This research only refers to data available in SAP based on performance in 2022 without counting the return part from reject customer and reject part caused by supplier. Contribution: Implementing core problem solving (CPS) combined with the Kepner Treg approach showing the right direction and good impact on quality performance at UTAS Bandung. It is important to develop an army of core problem-solving by encouraging more people to learn about it. This can also be used as a benchmark for other sites in global groups.